Correlations between serum levels of 25-hydroxyvitamin D and carotid atherosclerosis in patients with type 2 diabetes in Shanghai - Chen, Rui-hua; Jiang, Xiao-zhen; Jiang, Quan; Gu, Zhe; Gu, Pei-li; Zhou, Bin; Zhu, Zhen-hong; Xu, Lin-yan; Zou, Yu-feng (Annales d'endocrinologie, 2014)
To explore the potential association between the serum levels of 25-hydroxyvitamin D [25(OH)D] and carotid atherosclerosis in patients with type 2 diabetes. Three hundred and fifty patients with type 2 diabetes were enrolled in this study in Shanghai, China. B-mode ultrasound was used to detect carotid plaques as indicators of atherosclerosis and measure carotid artery intima-media wall thickness (C-IMT) at two sites of carotid artery. Subjects were divided into group A (patients with carotid plaques) and group B (patients without carotid plaques) and be assessed clinically. Serum levels of 25(OH)D and other clinical parameters were measured. Multivariate logistic regression was performed to find predictors of carotid atherosclerosis in the entire group. The levels of serum 25(OH)D were lower in group A than in group B[19.60 (13.30–25.73) vs 23.19 (18.10–30.06)ng/ml, P<0.001]. The C-IMT levels [(1.00±0.17 vs 0.88±0.20)mm, Ptrend<0.001] and proportion of people with carotid plaques(44/88 vs 20/87, Ptrend<0.001) in the lowest quartile of 25(OH)D were higher than in the highest quartile. Vitamin D concentrations were inversely associated with HbA1c in women(r=−0.194, P=0.006), and C-IMT in men(r=−0.409, P<0.001). Logistic regression analysis showed age, male sex, current smoke, history of hypertension, SBP, LDL-C and lg[25(OH)D] (OR: 0.924, 95%CI: 0.893–0.955, P<0.001) were independently associated with the presence of carotid plaques in T2DM. Serum vitamin D level is significantly and independently associated with carotid atherosclerosis in patients with T2DM in Shanghai, China. Explorer l’association potentielle entre les taux sériques de 25-hydroxyvitamine D [25(OH)D] et l’athérosclérose carotidienne chez les patients atteints de diabète de type 2. Trois cent cinquante patients atteints de diabète de type 2 ont été inclus dans cette étude menée à Shanghai, en Chine. L’échographie en mode B a été utilisée pour détecter les plaques carotidiennes indiquant une athérosclérose et mesurer l’épaisseur de la paroi intima-média carotidienne (C-IMT) en deux endroits de l’artère carotide. Les patients ont été divisés en groupe A (patients atteints de plaques carotidiennes) et groupe B (patients sans plaques carotidiennes) et évalués cliniquement. Les niveaux sérologiques de 25 (OH) D et d’autres paramètres cliniques ont été mesurés. Une régression logistique multivariée a été effectuée pour trouver des prédicateurs de l’athérosclérose carotidienne dans l’ensemble du groupe. Les taux sériques de 25(OH)D étaient plus faibles dans le groupe A que dans le groupe B [19,60 (13,30 à 25,73) vs 23,19 (18,10 à 30,06)ng/mL, p<0,001]. Les niveaux C-IMT [(1,00±0,17 vs 0,88±0,20)mm, p<0,001] et la proportion des patients avec plaques carotidiennes (44/88 vs 20/87 p<0,001) dans le quartile le plus bas de 25(OH)D étaient plus élevés que dans le quartile le plus élevé. Les concentrations en vitamine D étaient inversement associées à l’HbA1c chez les femmes (r=−0,194, p=0,006), et C-IMT chez les hommes (r=−0,409, p<0,001). L’analyse de régression logistique a montré que l’âge, le sexe masculin, le tabagisme, des antécédents d’hypertension, la pression artérielle systolique, le LDL-C et une lg [25(OH)D] (OR: 0,924, IC à 95 %: 0.893–0 0,955, p<0,001) étaient associés d’une façon indépendante avec la présence de plaques carotidiennes dans le DT2. Le taux sérique de vitamine D est significativement et indépendamment associé à une athérosclérose carotidienne chez les patients atteints de DT2 à Shanghai.